A Vicious Cycle: In Severe and Critically Ill COVID-19 Patients - Huang, Peifeng; Zuo, Qingwei; Li, Yue; Oduro, Patrick Kwabena; Tan, Fengxian; Wang, Yuanyuan; Liu, Xiaohui; Li, Jing; Wang, Qilong; Guo, Fei; Li, Yue; Yang, Long (Frontiers in Immunology, 2022)
COVID-19 is resulted from SARS-CoV-2 infection, causing worldwide epidemic. Severe inflammatory response and venous thrombosis are commonly noted in COVID-19 patients with severe and critically illness, leading to poor prognosis. IL-6 as a major inflammatory cytokine is an independent factor in predicting the severity of patients with COVID-19, due to incorporating with TNF-α in the cytokine storm, promoting endothelial cell damage, upregulating PAI-1 levels, and has significant differences in serum isolated from mild and severe COVID-19 patients. IL-6 and PAI-1 form a vicious cycle between inflammatory and thrombosis, which may be the main cause of the poor prognosis in patients with severe COVID-19. Targeted inhibition of IL-6 and PAI-1 signal transduction appears to treat severe and critically ill COVID-19 patients suffering cytokine storms and venous thrombosis more effectively, which is likely to promote the study of the relationship between inflammatory cytokines and thrombosis in Viral Immunology, and will be beneficial for critically-ill patients with COVID-19 worldwide.